Selective Membrane Toxicity of the Polyene Antibiotics: Studies on Lecithin Membrane Models (Liposomes) - Hsuchen, Chuen-Chin (1973)
In the absence of sterol, amphotericin B at 5 × 10(−6) M caused maximum marker release from the saturated dipalmitoyl lecithin liposomes, minimum release from the unsaturated dioleoyl lecithin liposomes, and an in-between response from egg lecithin liposomes. Nystatin at 2.5 to 4.0 × 10(−5) M induced appreciable marker release from all three types of sterol-free liposomes. The amphotericin B- and nystatin-induced permeability changes in dipalmitoyl lecithin liposomes were drastically suppressed by the incorporation of cholesterol or stigmasterol (with identical Δ5 sterol nuclei), but were unaffected by the incorporation of ergosterol or 5,7-cholestadien-3β-ol (with identical Δ5,7 sterol nuclei). The nystatin sensitivity of dioleoyl lecithin liposomes remained low after the incorporation of cholesterol or stigmasterol, but was greatly enhanced by the incorporation of ergosterol or 5,7-cholestadien-3β-ol. Digitonin, a compound known to interact specifically with membrane sterol, induced marker release from liposomes in proportion to the amount of either cholesterol or ergosterol incorporated; epicholesterol did not sensitize to digitonin. These results lead to the following conclusions: (i) polyene-induced permeability alteration in model membrane systems is effected by the composition of membrane phospholipid fatty acyl chains; (ii) the distribution of double bonds in the sterol nucleus is related to the selective toxicity of the polyenes toward natural sterol-containing membranes; and (iii) polyenes differ in membrane selectivity.